Solid pseudopapillary neoplasms of the pancreas (SPNs): diagnostic accuracy of CT and CT imaging features - Ming Zhao; Jie Wang; Jiejuan Lai; Fenghao Liu; Yujun Zhang; Li Cao; Li Liu; Kuansheng Ma; Jianwei Li; Qingsong Deng (World Journal of Surgical Oncology, 2024)
Abstract Purpose To summarize the abdominal computed tomography (CT) imaging and clinicopathological data of patients with SPNs of the pancreas and analyze the accuracy of preoperative CT diagnosis and features. Materials and methods Between June 2006 and June 2023, CT images of 120 histopathologically proven SPNs in the pancreas were retrospectively reviewed. Fifteen features, including age, sex, and CT-determined features, were included in a multiple stepwise regression analysis. The correlations between features and SPNs, including odds ratios (ORs) and 95% confidence intervals (CIs), were evaluated. Results Among the 120 patients, the diagnostic accuracy of CT was 43.3%. The baseline CT results of patients with a correct diagnosis and misdiagnosis revealed significant differences in sex (P = 0.043), age (P = 0.004), boundary (P = 0.037) and encapsulation (P = 0.002) between the two groups. The preoperative imaging diagnostic accuracy was significantly greater in females than in males (47.9% vs. 25.0%, P = 0.043). The immunohistochemical indices did not significantly differ between the two groups. The results of univariate analysis revealed significant differences in sex (P = 0.048), age (P = 0.014), tumor length (P = 0.023), tumor boundaries (P = 0.039) and capsule type (P = 0.003). The results of multivariate analysis revealed that encapsulation was closely related to the diagnostic accuracy of CT (P = 0.04). Conclusions The accuracy of CT in the diagnosis of SPNs is low, but a length‒diameter ratio of the tumor approaching 1.0, encapsulation and clear boundaries are important CT-determined features. The capsule is an independent CT predictor in the diagnosis of SPNs.